Atuação de psicólogos nos Centros de Referência de Assistência Social CRAS: (im)possibilidades - Carretero, Gustavo Henrique (2018)
This research has as theoretical reference the Critical Social Psychology, on the Marxist bases, on the capitalist society. Its object of study is the work of the psychologist in the Centers of Reference of Social Assistance (CRAS) that allowed the entrance of this professional in the welfare public policy, and aims to: analyze the (in) possibility of CRAS to be a space of psychosocial transformative and emancipatory action by the social psychologist, considering the contradictions of his work in this field and his relations with the state, society and capitalist ideology. The research was carried out through analysis of legislation, guidelines of the Ministry of Social Development, texts of the Federal Council of Psychology, scientific articles and development of narrative of the experience of the researcher as a psychologist in CRAS. It seeks to reflect on the contradictions of capitalist society, social issue, public policies, Brazilian social formation, welfare public policy, psychological practices. It has demonstrated the tenuous frontier of the psychosocial practices developed in this field between actions of assistencialismo, clientelistic, and reproductive character of heteronomy and empowering actions of emancipation and social participation, a frontier that is often diluted in ambiguities and contradictions. Its central idea is that the work of the psychologist in CRAS has (im) possibilities that refer to professionals, institutional issues, psychology, public policies, welfare and capitalism. The results demonstrated that the work in social policies presents limitations on structural transformation of reality, but that in the long term civilizational advances can be achieved in Brazil in social and subjective terms. It is proposed the realization of a critical social work with families, having as object the ethic-political malaise through listening, acting and guarantying rights. Thus, in the meeting between public policies and Psychology the internal contradictions of the two fields produce new tensions and possibilities of new configurations (progressivity as conservative) in both